Correction of temperature errors due to the unknown effect of window transmission on ratio pyrometers using an in situ calibration standard. (May 2015) - Lowe, Dave; Machin, Graham; Sadli, Mohamed
Abstract: Ratio pyrometers are widely used for non contact temperature measurement in situations where non-blackbody conditions exist. A high temperature fixed-point cell based on rhenium–carbon alloy was used to characterise the effect of window contamination based on the simplest assumption that graybody conditions existed. A visible-near IR spectrometer was used to mimic the behaviour of a ratio pyrometer. The deposition of particulate contamination on clean glass windows was found to substantially change the indicated temperature. This change is liable to be unpredictable. The use of an in-process reference fixed-point cell was tested and found to give potential for significant reduction of errors across a wide temperature range.